Weekly Fluctuations in College Student Leisure Activities and Well-Being - Doerksen, S.; Elavsky, S.; Rebar, Amanda; Conroy, D. (Routledge, 2014)
College students' well-being is declining. Differences in students' leisure activity participation have been linked to their psychological well-being. This study examined how weekly fluctuations in leisure allocation (i.e., frequency of volunteer, cognitive, social, club, religious, and physical activities) related to well-being in college students. Students completed weekly leisure time allocation assessments. Generalized linear multilevel analyses showed that time allocation and well-being varied within-people. Fluctuations in leisure time allocation were related to fluctuations in well-being. Findings extend understanding of leisure and well-being by highlighting the unique contributions of within-person fluctuations beyond between-person differences. © 2014 Copyright Taylor and Francis Group, LLC.